Parameters and outcomes in 525 patients operated on for oral squamous cell carcinoma. Issue 9 (September 2016) - Garzino-Demo, P.; Zavattero, E.; Franco, P.; Fasolis, M.; Tanteri, G.; Mettus, A.; Tosco, P.; Chiusa, L.; Airoldi, M.; Ostellino, O.; Schena, M.; Rampino, M.; et al.
Abstract: Purpose: This report analyzed the outcomes of patients undergoing surgery for oral squamous cell carcinoma (OSCC) to identify the value of prognostic factors. Material and methods: A total of 525 patients were studied who had undergone surgery for oral squamous cell carcinoma (OSCC) between 2000 and 2011, of whom 222 had received postoperative radiation-therapy (PORT) and or chemoradiation-therapy (PORTC). For each patient, personal data, histological findings, treatment and outcome were recorded and analyzed statistically. Survival curves were calculated using the Kaplan–Meier algorithm, and the difference in survival among subgroups was examined. Results: The overall survival (OS) and disease-specific survival (DSS) 5-year survival rate in the 525 patients were respectively 71.38% and 73.18%. The differences in the overall survival and disease-specific 5-year survival were significant (p < 0.05) for age < 40 years, site of origin, N status, staging, grading, osseous medullar infiltration, and perineural invasion. In patients undergoing radiation therapy, only perineural invasion negatively influenced the survival prognosis. In 150 pT1 cases of tongue and floor-of-mouth cancer, an infiltration depth (ID) > 4 mm was statistically correlated with poorer prognosis. Conclusions: The results demonstrate an improvement in the 5-year OS and DSS rates during the past decade compared with the previous decade. Univariate analysis revealed that age, tumor staging, and lymph node involvement, extracapsular spread, grading, perineurial invasion, infiltration depth, and osseus medullary invasion were associated significantly with overall survival and disease-specific survival.